33. KNOWLEDGE OF HEALTH REPORT STATISTICS AMONG COMMUNE HEALTH STATION STAFF IN HAU LOC AND QUANG XUONG DISTRICTS, THANH HOA PROVINCE, 2024, AND RELATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Objective: to assess knowledge of health report statistics among commune health station staff in Hau Loc and Quang Xuong districts, Thanh Hoa Province, and to examine related factors.Methodology: A cross-sectional study was conducted at 48 commune health stations in Hau Loc and Quang Xuong districts from January 2024 to February 2025. Data were collected via a standardized questionnaire developed based on healthcare regulations and expert input.Results: Of the 234 participants (response rate: 83,5%), 57.3% demonstrated adequate knowledge of health report statistics. Knowledge levels were significantly higher in Quang Xuong (63.4%) than in Hau Loc (36.6%, p
Keywords: Health report statistics; healthcare staff knowledge; primary healthcare; Thanh Hoa; logistic regression